Cloud-based implementation of an automatic coverage estimation methodology for self-organising network - Fernandes, D. (2020)
One of the main concerns of telecommunications operators are related to the network coverage. A weak coverage can lead to a decrease, not only in the user experience when using the operators’ services such as multimedia streaming, but also decreases the overall Quality of Service. This paper presents a novel cloud-based framework of a semi-empirical propagation model that estimates the coverage in a precise way. The novelty of this model is that it is automatically calibrated by using drive test measurements, terrain morphology, buildings in the area, configurations of the network itself and key performance indicators automatically extracted from the operator’s network. Requirements and use cases are presented as motivations for this methodology. The results achieve an accuracy of about 5 dB, allowing operators to obtain accurate neighbour lists, optimise network planning and automate certain actions on the network by enabling the Self-Organising Network concept. The cloud implementation enables a fast and easy integration with other network management and monitoring tools, such as the METRIC platform, optimising operators’ resource usage recurring to elastic resources on-demand when needed. This implementation was integrated into the METRIC platform, which is currently available to be used by several operators.